Habitat Characteristic of Softshell Turtle (Amyda cartilaginea Boddaert,1770) in Engkelitau River Sekadau Regency, West Borneo - Arbi, Florensius Joko; Yanti, Ari Hepi; Riyandi, Riyandi (Jurnal ILMU DASAR, 2021)
Information about the character of softshell turtle’s habitat (Amyda cartilaginea) is needed as conservation effort and to prevent softshell turtle’s extinction. The research on habitat, morphometric holes, and environmental factors that suitable for softshell turtle is needed to be approved. The research was conducted in Engkelitau River, Sekadau, West Borneo. Sampling area was divided into 3 stations based on the type of cover between primary dryland forest, farming land and open field. Data on the softshell turtle’s number, holes and scratch marks were analyzed using principal component analysis (PCA). The highest river slope at Station I is 60o and the lowest river slope at Station III is 42o. Substrate’s type that found in Engkelitau River consist of sandy, dusty, and muddy substrates. The number of softshell turtle’s hole in the Engkelitau River is 45 holes, consisting one hole with softshell turtle, 15 holes with scratch marks, and 29 holes not including both of them. The highest height, width and distance between holes are in Station I and both hole’s length and height from the surface as well as highest river are in Station II. The environmental factors that affected A. cartilaginea in the Engkelitau River consisted of river velocity and river’s slope with loading factors of 4.08135 and 3.94019 respectively. The characteristics of A. cartilaginea’s hole in the Engkelitau River including a pond in the hole, an air hole, and located in the middle of a riverbank. Keywords: habitat characteristics, Amyda cartilaginea, softshell turtle, Engkelitau river.